(untitled) (Swiss Medical Weekly, 2025)
BACKGROUND AND AIMS: Respiratory syncytial virus (RSV) infection is one of the leading causes of hospitalisation in infants, the elderly and immunocompromised patients, with significant morbidity and mortality rates. Despite its global impact, epidemiological surveillance of RSV in Switzerland has historically been limited compared to the USA and European countries. A significant surge in RSV activity and hospitalisations after the COVID-19 pandemic, along with the introduction of new monoclonal antibodies and RSV vaccines, has led to an increased interest in the molecular epidemiology of RSV. To ensure continued efficacy of the new preventive options, monitoring of the genetic diversity of circulating RSV strains, their evolutionary dynamics and the potential emergence of resistance mutations is of central importance. The present study aimed to characterise the genetic diversity and seasonal trends of RSV dynamics in Switzerland from 2019 to 2024, mainly over the last two post-pandemic winter seasons (2022/23 and 2023/24). METHODS: A total of 48,897 respiratory clinical specimens from 30,782 patients with respiratory tract infections were tested for RSV at a tertiary care centre in Northwestern Switzerland between July 2019 and June 2024. RSV activity over these seasons was investigated. Amplicon-based whole-genome sequencing was performed on 182 selected samples, with 125 high-quality consensus genomes and phylogenies reconstructed. Lineage distribution and seasonal subtype prevalence were compared to European data. RESULTS: RSV activity was absent during the 2020/21 pandemic season, but surged with an off-season peak in summer 2021. RSV B predominated during the 2022/23 season, while a shift to RSV A occurred in the 2023/24 winter season, which is in line with neighbouring European countries. Lineage subtype distribution showed high concordance with circulating European strains. RSV A exhibited greater diversity (mean pairwise Hamming distance 0.015, SD 0.006) than RSV B (mean 0.006, 0.003), with all current strains falling within G protein duplication clades A.D.1, 2, 3 and 5 for RSV A, and B.D.E.1 and B.D.4.1.1 for RSV B. CONCLUSION: By contributing 125 newly assembled RSV genome sequences, we have significantly increased the number of publicly available whole-genome sequences from Switzerland. Our study provides a genomic surveillance of RSV in Switzerland, analysing seasonal patterns, alternating subtype dominance, and consistency with broader European trends. A comprehensive understanding of the molecular epidemiology of RSV enables healthcare providers and public health authorities to monitor the effectiveness of current vaccines and monoclonal antibodies, associate lineages and serotypes with disease severity, implement timely interventions and detect emerging variants, ultimately reducing the burden of RSV-related illnesses.